Contribution of the Scientific School of Saint Petersburg Electrotechnical University in the Field of Optimal Discrete Signal Design - V. P. Ipatov (Известия высших учебных заведений России: Радиоэлектроника, 2023)
Introduction. Numerous modern infocommunication systems are based on the spread spectrum technology, i. e., on the use of signals with a large bandwidth-duration product. Many such systems implement discrete signals, which are sequences of standard pulses manipulated in phase and amplitude. The design of code sequences for such signals is a fairly knowledge-intensive task requiring a serious mathematical apparatus. This review presents the results of Saint Petersburg Electrotechnical University school in the field of synthesis of code sequences with ideal or nearly ideal autocorrelation, as well as code ensembles for CDMA networks.   Aim. To acquaint the reader with the results of long-term research carried out by Saint Petersburg Electrotechnical University school in the field of discrete signal design.   Materials and methods. The materials under review included the publications of specialists from the Radio System Department of Saint Petersburg Electrotechnical University and those published by domestic and foreign researchers on the corresponding topics. The major focus was to review the most theoretically significant texts published in leading domestic and foreign journals over the past four decades, leaving applied studies, copyright certificates and patents outside the scope of the review. At the same time, the review included those foreign publications of applied nature that are significant for the development of information and communication projects.   Results. The reviewed publications significantly expand the range of discrete signals that are promising for wireless infocommunication applications.   Conclusion. Solutions of a number of the studied topical problems to design sequences with the necessary metric properties are of an original nature and great practical importance.